Paradigm shift for Project Managers in Agile Projects (International Journal of Engineering and Computer Science, 2013)
IT Managers are always under pressure to meet deadlines and deliver timely results either in form of fully functional applications or improvements and changes in them. Despite budget slashes and economic downturns, IT companies must struggle to keep up with the pace of change and continue delivery. A possible solution to this conundrum is Agile software development methodologies which help IT companies plan and execute their projects by meeting changing scenarios head on and assuring rapid delivery while being flexible and maintaining quality.